1999
DOI: 10.1210/jcem.84.11.6148
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the Polycystic Ovary Syndrome in the Greek Island of Lesbos: Hormonal and Metabolic Profile

Abstract: Polycystic ovary syndrome (PCOS) is characterized by hyperandrogenism, chronic anovulation, and oligomenorrhea (O/M). PCOS has variable clinical phenotypes, biochemical features, and metabolic abnormalities. To determine the prevalence of PCOS in the Greek population as well as the metabolic parameters, we performed a cross-sectional study of 192 women of reproductive age (17-45 yr), living on the Greek island of Lesbos. They were divided into 4 groups according to the presence of hirsutism (defined as a Ferri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
231
5
29

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 799 publications
(284 citation statements)
references
References 27 publications
4
231
5
29
Order By: Relevance
“…Women of reproductive age are affected by polycystic ovary syndrome (PCOS) by w5-7% depending on ethnicity and diagnostic criteria (1,2). In a community sample, the prevalence of PCOS according to the Rotterdam criteria was shown to be w12% and increased to w18% when imputed values of the number of women with polycystic ovaries in the group that did not have ultrasound were included (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Women of reproductive age are affected by polycystic ovary syndrome (PCOS) by w5-7% depending on ethnicity and diagnostic criteria (1,2). In a community sample, the prevalence of PCOS according to the Rotterdam criteria was shown to be w12% and increased to w18% when imputed values of the number of women with polycystic ovaries in the group that did not have ultrasound were included (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is the most common endocrinopathy in reproductive aged women, affecting around 6-20% of said population (1,2). It is a metabolic disorder characterised in a high percentage of cases by insulin resistance (IR) (3), which means that patients are at a high risk of developing type 2 diabetes (4) or metabolic syndrome (5).…”
Section: Introductionmentioning
confidence: 99%
“…It is most common in women of reproductive age (Diamanti-Kandarakis et al 1999). A meeting of experts in Rotterdam in 2003 suggested that the definition of PCOS should include two of the following three criteria: (1) oligo-and/or anovulation, (2) clinical and/or biochemical signs of hyperandrogenism, and (3) polycystic ovaries on ultrasonography and exclusion of related disorders (Rotterdam ESHRE/ASRM-Sponsored PCOS Consensus Workshop Group 2004).…”
Section: Introductionmentioning
confidence: 99%